Strategi Pendidikan Karakter Perspektif Kh. Hasyim Asy’ari (Kajian Kitab Adabul Alim Wa Muta’allim) - Abdul Muhaimin (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2017)
This study examines the thinking of KH education. M. Hasyim Asy'ari in applying character education methods and strategies. The authors limit the study of A> da> b al-'A> lim wa Muta'allim by KH. M. Hasyim Asy'ari. The results showed that, firstly, 1) The strategy used in the application of character education perspective KH. M. Hashim Asy'ari in the book Ada> b al-'A> lim Wa al-Muta'allim there are two kinds: spiritual strategy (batiniyah) and non-spiritual strategy (lahiriyah). Non-spiritual strategy (lahiriyah) done by KH. M. Hasyim Ash'ari there are three kinds: related to the model figure: uswah hasanah strategy, related curriculum: integration and internalization strategy, related to methodology: forced formality strategy and define-and-drill strategy 2) The method used in applying KH perspective character education . M. Hashim Ash'ari in the book A> da> b al-'A> lim wa al-Muta'allim is: Mauidhah or lecture method, targhi method <b wa al-tarhi <b, modeling method or al-qudwah h asanah / uswah h asanah, moralizing methods, methods of practice or tajribah.